ANALISIS PSIKOLOGI BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA BERDASARKAN TEORI KOGNITIF, KONSTRUKTIVISTIK, DAN BEHAVIORISTIK - Nona Musi; Claudia Riwu; Maya Miyi; Yofin Noning; Elsi Bay; Nurul Mansur; Nelson Epu; Hilaria Mbagho (Almeera Education, 2026)
This study aims to analyze the psychology of student learning in mathematics learning based on cognitive, constructivist, and behaviorist theories in Grade IIA students of SDI Onekore 5. The study employed a descriptive qualitative approach through structured observation of 20 students present out of 22 enrolled. The data collection instrument included an observation sheet covering five aspects: attention, comprehension, response, interaction, and learning speed. Results show variations in student comprehension levels: 5 students (25%) in the high category, 10 students (50%) in the moderate category, and 5 students (25%) in the low category. Cooperative learning through group discussion proved effective in enhancing student understanding, reflecting the application of Vygotsky's constructivist theory through the Zone of Proximal Development (ZPD). The use of video media, analog clock props, quizzes, and reflection reflects behaviorist stimulus-response principles and Piaget's cognitive concrete representation. The main finding is that all three learning psychology theories can be synergistically identified within a single learning session. This research contributes to the understanding that an integrated approach is more effective than applying a single theory exclusively in elementary school mathematics learning.